The effect of education, training, and promotion on employee performance through job satisfaction in the inspectorate of Tanjungpinang City and Bintan District - Haryanto, Eko; Wibisono, Chablullah; Catrayasa, I Wayan; Ngaliman, Ngaliman; Indrawan, Muhammad Gita (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: The purpose of this study is to examine the relationship between education, training, and promotion on employee performance, mediated by job satisfaction. Methodology: The study utilizes a quantitative research methodology involving survey questionnaires administered to employees in the Inspectorate of Tanjungpinang City and Bintan District. Results: The results demonstrate a positive relationship between education, training, promotion, and job satisfaction. Job satisfaction also mediates the relationship between these variables and employee performance. By identifying the impact of education, training, and promotion on job satisfaction and employee performance, this study provides insights for organizations to improve human resource management practices and optimize performance. Conclusions: The findings highlight that education, training, and promotion significantly influence job satisfaction, which in turn enhances employee performance. Organizations must prioritize investment in these areas to create a motivated and productive workforce. Limitations: This study is limited by the sample size and geographical scope, impacting the generalizability of the findings. Reliance on self-reported data may also introduce bias, and external factors beyond the study’s control could affect outcomes. Contribution: This research enriches scholarly discourse by offering a nuanced understanding of how education, training, and promotion collectively impact employee performance through job satisfaction. It also provides practical recommendations for organizational stakeholders to design policies and programs that support sustainable employee development and performance improvement.